Big Data Analysis of Skill Requirements in the Indonesian Manufacturing Sector: A Semantic Approach Using Large Language Models - Muhammad Akbar; Ni Luh Saddhwi Saraswati Adnyani; Rubanto Sidi Hambaly (Institute of Research and Community Outreach - Petra Christian University, 2026)
The rapid acceleration of Industry 4.0 has fundamentally reshaped industrial competency demands, resulting in the